Broadening the phenotypic spectrum of EVEN‐PLUS syndrome through identification of HSPA9 pathogenic variants in the original EVE dysplasia family and two sibs with milder facial phenotype. Issue 9 (2nd July 2022) - Pacio‐Miguez, Marta; Parrón‐Pajares, Manuel; Gordon, Christopher T.; Santos‐Simarro, Fernando; Rodríguez Jiménez, Carmen; Mena, Rocio; Rueda Arenas, Inmaculada; F. Montaño, Victoria Eugenia; Fernández, María; Solís, Mario; del Pozo, Ángela; Amiel, Jeanne; et al.
Abstract: EVEN‐PLUS syndrome is a rare autosomal recessive disorder caused by biallelic pathogenic variants in the mitochondrial chaperone called mortalin, encoded by HSPA9 . This genetic disorder, presenting with several overlapping features with CODAS syndrome, is characterized by the involvement of the Epiphyses, Vertebrae, Ears, and Nose (EVEN), PLUS associated findings. Only five individuals presenting with the EVEN‐PLUS phenotype and biallelic variants in HSPA9 have been published. Here, we expand the phenotypic and molecular spectrum associated with this disorder, reporting two sibs with a milder phenotype and compound heterozygous pathogenic variants (a recurrent variant and a novel one). Also, we confirm a homozygous pathogenic variant in the family originally reported as EVE dysplasia.